(untitled) (Lapai Journal of Economics, 2024)
The study examines the impact of Revenue on Budget Implementation in Nigeria with particular reference to Federal Capital Territory Administration (FCTA). The data was obtained from secondary sources. The variables studied were Actual Total Expenditure as dependent variable while Actual Recurrent Revenue Receipt and Actual Capital Receipt as independent variables. The methodology employed was OLS regression model. The Result suggests that, the Actual Recurrent Revenue Receipt has a positive and significant impact on Budget Implementation. On the other hand, Actual Capital Receipt had a positive but insignificant impact on Budget Implementation. The researcher concludes that Actual Recurrent Revenue Receipt and Actual Capital Receipt have positive impact on Budget Implementation; however, bureaucratic bottleneck militates against budget implementation efficiency. In view of that, the study recommends that, there is need for increase in capital grants to enhance capital receipts in order to finance capital projects. FCTA should improve on its revenue collection by exploring other sources of Internally Generated Revenue (IGR) like Property Taxes on unoccupied estates in the city so as to boost performance in revenue collection and improve on collection of water bills etc. Relying on the existing tax base, FCTA can maximize on the collection of taxable (withholding tax etc.) and vatable items on goods, supplies and services through proper inspection of taxable and valuable items before payment to all and sundry. There is also the need for digitization of the budget system, incentives and adequate training to serve as motivation, improve capacity, collection of revenues, enhance the budget preparation exercise and implementation, as well as to guard against all sorts of behaviors.